Controlled trial of intravenous corticosteroids in severe acute asthma. Issue 8 (August 1992) - Morell, F; Orriols, R; de Gracia, J; Curull, V; Pujol, A
Abstract : BACKGROUND: The value of corticosteroids in severe acute asthma continues to be debated. METHODS: Ninety consecutive patients admitted to the emergency room with severe acute asthma were studied in a randomised, double blind, controlled trial to determine the efficacy of corticosteroids. Eighty two patients completed the study. All received oxygen therapy and intensive bronchodilator treatment. The patients were divided into three groups for steroid treatment, receiving intravenous methylprednisolone 10 mg/kg every four hours for 48 hours (29 patients, group A); intravenous methylprednisolone 2 mg/kg every 4 hours for 48 hours (27 patients, group B); or no intravenous corticosteroids (26 patients, group C). RESULTS: There were no differences on admission among the three groups in forced expiratory volume in one second (FEV1), forced vital capacity (FVC), peak expiratory flow (PEF), or arterial oxygen or carbon dioxide tension; and the rates of recovery in FEV1, FVC, and PEF were similar. CONCLUSIONS: Corticosteroids given with bronchodilators have not shown a beneficial effect in the first 48 hours of recovery of severe acute asthma. Only in those patients who failed to respond by the third hour of treatment, and in those who were previously taking oral corticosteroids, does a favourable, though not statistically significant, effect appear to occur.